MEMBANGUN HUKUM PERJANJIAN JUAL BELI SECARA BERKALA YANG ADIL BAGI PARA PIHAK - Heri Purnomo; Agnes Maria Janni (Fakultas Hukum Universitas 17 Agustus (UNTAG) Semarang, 2021)
Nowadays, in line with technological advances in the field of transportation and telecommunications, in a developing society various new legal institutions are widelyused in practice in our country, namely what we know as periodic sale and purchaseagreements. Judging from the seller's point of view, the emergence of this form of agreement certainly does not cause too many problems. However, it feels safe when viewed from the seller's point of view, it is not the case with the situation felt by the buyer. There are many problems faced by buyers as a result of making regular sale and purchase agreements, especially when we look at the portrait of buyers who make periodic sales and purchase agreements, most of them are buyers whose economic conditions are weak. From the background of the problems that become the problem are: 1) How is the legal protection for buyers who suffer losses due to the making of a periodic sale and purchase agreement 2) How to build a fair law for the parties in a periodic sale and purchase agreement? From the results of the study of the above problems, it can be seen that the main legal protection for buyers is torefer to the contents of the agreement made by the parties and the Consumer Protection Law as its legal umbrella, while efforts to build a fair law for the parties certainly need to pay attention to the existence of various principles underlie the making of an agreement such as the principle of good faith that underlies the making of an agreement.